Positivity: A key for enhancing creativity. Enhancing organizational creativity through positive leadership - Fjóla Björk Hauksdóttir 1974- (2011)
This research explored how creativity can be enhanced through leadership. Specifically, what specific leader behaviour encourages employee creativity and why. Using a qualitative case-based study, nine interviews were conducted in three companies in the creative industry in Iceland: CCP, CAOZ and the Icelandic Advertising Agency. The results indicate that positivity (the quality of having a positive mindset) is a key behavioral contributor to enhanced creativity. Positivity was found to positively influence employee psychological well-being as well as motivation. Both motivation and psychological well-being were found to be important conditions for creativity to flourish. Positivity was also found to have a positive ripple effect throughout the organization, enhancing espirit de corps, including the feeling of group membership, positive social interactions, treating people with respect, setting higher goals, increased effort and work enjoyment as well as overall organizational performance. Positive leadership may thus be instrumental for an organization to reach extraordinary performance.